Post-amputation neuroma of radial nerve in a patient with ephitelioid sarcoma: case report and literature review: POST-AMPUTATION NEUROMA OF RADIAL NERVE - Sandomenico, Fabio; Corvino, Antonio; Setola, Sergio Venanzio; Simonetti, Igino; Porcaro, Mauro; Trovato, Piero; Catalano, Orlando; Petrillo, Antonella (Acta Biomedica Atenei Parmensis, 2020)
Neuroma, also known as traumatic neuroma or amputation neuroma or stump neuroma, is a focal non neoplastic area of proliferative hyperplastic reaction secondary to peripheral nerve damage that commonly occurs after a focal trauma (acute or chronic) or surgery, such as amputation or partial transection. Neuromas are more commonly located in the lower limbs, followed by head and neck; other extremely rare sites include the ulnar nerve followed by the radial nerve and the brachial plexus. A radiologic plan is necessary to recognize soft tissue lesions with a neural origin and whether they are a true tumor or a pseudotumor such as a neuroma, fibrolipoma, or peripheral nerve sheath ganglion. In oncologic patients the appearance of post-surgical neuromas can produce problems in differential diagnosis with local recurrences. Therefore, with a combination of different imaging techniques, mainly ultrasound (US) and magnetic resonance imaging (MRI), it is possible to characterize neurogenic tumours safely, with a great impact on patient management and to plan an appropriate treatment. Here, we report the first case of post-amputation neuroma of radial nerve in a patient with clinical history of ephitelioid sarcoma with a short literature review.